2007
DOI: 10.1002/humu.20600
|View full text |Cite
|
Sign up to set email alerts
|

Closely linkedcis‐acting modifier of expansion of the CGG repeat in high riskFMR1haplotypes

Abstract: Communicated by Pui-Yan KwokIn its expanded form, the fragile X triplet repeat at Xq27.3 gives rise to the most common form of inherited mental retardation, fragile X syndrome. This high population frequency persists despite strong selective pressure against mutation-bearing chromosomes. Males carrying the full mutation rarely reproduce and females heterozygous for the premutation allele are at risk of premature ovarian failure. Our diagnostic facility and previous research have provided a large databank of X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…This is in line with previous reports and has been discussed in Dombrowski et al (7). This reinforces the hypothesis of a cis ‐acting genomic element influencing FMR1 instability other than the triplet‐repeats themselves (36) since the vast majority of such alleles have two AGG interruptions in the FMR1 triplet array (7, 37). With respect to transmission instability, we detected a statistically significant effect of haplotypes on instability, even for these unselected samples from the general population.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous reports and has been discussed in Dombrowski et al (7). This reinforces the hypothesis of a cis ‐acting genomic element influencing FMR1 instability other than the triplet‐repeats themselves (36) since the vast majority of such alleles have two AGG interruptions in the FMR1 triplet array (7, 37). With respect to transmission instability, we detected a statistically significant effect of haplotypes on instability, even for these unselected samples from the general population.…”
Section: Discussionsupporting
confidence: 92%
“…As Ghana represents an older and more diverse population, haplotype analyses may not provide additional hints with respect to susceptibility factors due to weak linkage disequilibrium (LD), as suggested previously for studies among African Americans (Crawford et al , 2000c, Eichler et al , 1994b). Further, recently identified cis-elements may be difficult to identify if LD is reduced (Beilina et al , 2004, Entezam & Usdin, 2008, Ennis et al , 2007). A complementary study of the frequency and haplotype backgrounds of chromosomes with the expanded fragile X mutation in the Ghanaian population would be useful to further characterize potential mutational pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A role for cis -acting factors in expansion is suggested by the fact that in many of the repeat expansion diseases some haplotypes are more likely to expand than others (Ennis et al ., 2007; Martins et al ., 2008; Murray et al ., 2000; Richards et al ., 1992; Takiyama et al ., 1995; Warby et al ., 2009). In addition, a comparison of different CAG/CTG triplet repeat loci indicated that the flanking CG content and proximity to CpG islands modifies the repeat expandability (Brock et al ., 1999; Nestor & Monckton, 2011).…”
Section: Repeat Expansions Cause Human Diseasementioning
confidence: 99%